2022
DOI: 10.1186/s12933-022-01670-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between abdominal obesity indices and risk of cardiovascular events in Chinese populations with type 2 diabetes: a prospective cohort study

Abstract: Background Waist circumference (WC), visceral adiposity index (VAI), lipid accumulation product (LAP), and Chinese visceral adiposity index (CVAI) are considered surrogate indicators of abdominal fat deposition, but the longitudinal association of these indices with cardiovascular (CV) events in adults with type 2 diabetes (T2D) remains unclear. Our study aimed to examine the associations between abdominal obesity indices and incident CV events among people with T2D and to compare their predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 55 publications
7
40
1
1
Order By: Relevance
“…Studies have demonstrated that abdominal obesity is linked to target organ damage in diabetes. 58,59 Our results confirmed that abdominal obesity is linked to altered brain function among T2D patients. The study provides evidence of interventions targeting abdominal obesity and regulating glucose and lipid metabolism during the mid-life of T2D patients.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have demonstrated that abdominal obesity is linked to target organ damage in diabetes. 58,59 Our results confirmed that abdominal obesity is linked to altered brain function among T2D patients. The study provides evidence of interventions targeting abdominal obesity and regulating glucose and lipid metabolism during the mid-life of T2D patients.…”
Section: Discussionsupporting
confidence: 80%
“…CVAI is an index for estimating visceral obesity based on Asian people, and external verification shows that it is positively correlated with VAT. Current studies show that CVAI performs well as an index of visceral obesity in predicting cardiovascular disease in the general population, and is superior to BMI, WC, and VAI [ 32 , 33 , 34 ]. However, the relationship between CVAI and CAS is unknown in steelworkers.…”
Section: Discussionmentioning
confidence: 99%
“…It is calculated from body mass index and waist circumference, as well as triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C) levels [ 4 ]. It shows an association with cardiovascular events [ 5 , 6 , 7 ]. Previously we reported that VAI tertiles were associated with calcium score, and the highest VAI tertile was an independent predictor for the presence of CACS > 100 in males [ 8 ].…”
Section: Introductionmentioning
confidence: 99%